Conservadorismo e democracia : pactos de razoabilidade - Pimentel, Pablo Fernando Campos (2022)
This work discusses, in a preponderant way, which type of mentality would best operate a regime of a democratic nature, since democracy is often said, however, most of the time, the speech can sound very amorphous. The objective of this text, however, is to defend the line of thought that goes in the following direction: it seems reasonable to think that the one that best contributes to the defense, maintenance and improvement of the regime called democracy, is the conservative mentality or predisposition. The idea strongly deepened here will take as a starting point, the classical conservatism that stems from Edmund Burke's central work, Reflections on the Revolution in France, where he severely criticizes the brutal and thoughtless destruction of institutions in 18th century France, in exchange for a complete innovation that could not be correctly estimated what could lead the people and the nation. The conservative mentality will, bluntly, bring seriously crucial aspects, it seems, to what positively and reasonably proves to be efficient in the good conduct of the democratic regime. This starting point will prove to be an adequate guideline for what will follow, with relevant thinkers such as T. S. Eliot, Michael Oakeshott and Russell Kirk. Fundamental themes such as: human nature, State, social contract, moral imagination, political rationalism, moral and political skepticism and culture will be developed in the thinkers that integrate the conservative mentality from its emergence with Burke until today. However, it is worth mentioning that issues related to the forms of configuration of democracy will be discussed, with the intention of establishing relations of efficiency or not with respect to the correct and incorrect, adequate and inadequate operation of the democratic system, since some formats of democracy they have been tried since their resurgence in the mid-19th century, and it does not seem to be the case that any of these models have achieved the desired success, either by their enthusiasts or by their critics. Conservatism and Democracy will be read, therefore, in the wake of what we proposed here to call the Pacts of Reasonableness, which can be understood as being those common ground, in which, regardless of the political side that one may be on, or even there is no appreciation mutual agreement between individuals, we should agree in a common way, without the need to promote constant political-ideological struggles. Therefore, this thesis will seek, through an adequate survey, to investigate elements in the conservative thinkers that make up this text, those central characteristics that outline, even if in general lines, proposals for pacts of reasonableness, with the intention of establishing a society in that, despite conflicts and disagreements between individuals, there are pacts or common contracts that no one wants to break, or that everyone understands to be of paramount importance to observe with reverence and respect.